Strategies For Digital Acceleration And Revitalization Of Msmes To Achieve Business Sustainability, Resilience, And Competitiveness - Sulistyanto, Tri Hadi; Utami, Indri Putri; Rachmawati, Silmi; Suryana, Salsa Billah Arianti (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
This study examines the urgency of digital transformation for Micro, Small, and Medium Enterprises (MSMEs) in Bekasi City as a strategy to achieve sustainability, resilience, and competitiveness. Although digitalization has been widely addressed in existing literature, limited attention has been given to localized strategies for digital acceleration and revitalization. To address this gap, a qualitative approach was applied using in-depth interviews with leaders of MSME associations, who simultaneously act as practitioners and stakeholders with comprehensive insights into the digitalization landscape. The data, collected from interview transcripts, were analyzed through keyword mapping and cluster analysis using Visualization of Similarity (VoS) software, allowing for a systematic exploration of recurring themes and interconnections. The findings indicate that, prior to the establishment of MSME associations, business activities were predominantly individual, limited, and traditional, with unstructured training opportunities, constrained market access, and insufficient digital literacy and equipment. The study further highlights that digital technologies serve as enablers for expanding market reach, while MSMEs require continuous support in the form of funding, technological equipment, and capacity-building programs. Digitalization emerges as an inevitable necessity for MSMEs to thrive in a rapidly evolving economic and technological environment. This research provides practical recommendations to guide stakeholders in formulating policies and strategies tailored to local needs, ultimately supporting digital acceleration and revitalization to foster sustainable MSME development.